Single-molecule microfluidic assay for prostate-specific antigen based on magnetic beads and upconversion nanoparticles - Sklenárová, Dorota; Hlaváček, Antonín; Křivánková, Jana; Brandmeier, Julian C; Weisová, Julie; Řiháček, Michal; Gorris, Hans H; Skládal, Petr; Farka, Zdeněk (Lab on a chip, 2024)
Early-stage diagnosis of prostatic carcinoma is essential for successful treatment and, thus, significant prognosis improvement. In laboratory practice, the standard non-invasive diagnostic approach is the immunochemical detection of the associated biomarker, prostate-specific antigen (PSA). Ultrasensitive detection of PSA is essential for both diagnostic and recurrence monitoring purposes. To achieve exceptional sensitivity, we have developed a microfluidic device with a flow-through cell for single-molecule analysis using photon-upconversion nanoparticles (UCNPs) as a detection label. For this purpose, magnetic microparticles (MBs) were first optimized for the capture and preconcentration of PSA and then used to implement a bead-based upconversion-linked immunoassay (ULISA) in the microfluidic device. The digital readout based on counting single nanoparticle-labeled PSA molecules on MBs enabled a detection limit of 1.04 pg mL-1 (36 fM) in 50% fetal bovine serum, which is an 11-fold improvement over the respective analog MB-based ULISA. The microfluidic technique conferred several other advantages, such as easy implementation and the potential for achieving high-throughput analysis. Finally, it was proven that the microfluidic setup is suitable for clinical sample analysis, showing a good correlation with a reference electrochemiluminescence assay (recovery rates between 97% and 105%).
Keywords: Prostatic Neoplasms; Prostate-Specific Antigen; mikrofluidní analytické techniky; limita detekce; mužské pohlaví; Immunoassay; Limit of Detection; lidé; Male; nanočástice; imunoanalýza; Humans; Microfluidic Analytical Techniques; Nanoparticles; nádory prostaty; prostatický specifický antigen